EVALUASI STRATEGI PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM DI SD NEGERI KECAMATAN BUNGA MAS BENGKULU SELATAN - Seten Hartedi (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
This study intends to determine the evaluation of instructional strategies teachers of Islamic religious education inpublic primary schools District of Bunga Mas South Bengkulu, with respondents graders VI totaling 130 people, an indicatorof study, the ability of human resources (teachers PAI), learning methods used, and the evaluation or assessment with a30 question questionnaire instrument. The purpose of this study was to: 1) describe the strategy of organizing learningIslamic Education, 2) describe the delivery strategy learning Islamic education, and 3) describe the learning managementstrategies of Islamic Education. This study uses qualitative research methods evaluative, the research has its own procedures,where such studies have exacting requirements that must be met such criteria, benchmarks, or standards that are usefulas a comparison for data or information obtained or is measurement. Collecting data using observation, questionnaires,interviews, and documentation. Data analysis techniques to the analysis of descriptive (describing what it is), namely by:data collection, data reduction, display data (data presentation), preparing research reports, and the conclusions of thestudy. Checking the validity of the data using an extension of observation, triangulation source and check. Research onthe evaluation of learning strategies of Islamic religious education teachers in public primary schools Bunga Mas Districtof South Bengkulu, with the results of the study are as follows: 1) organizing strategies of learning, values obtained withvery good category is 49%, good category is 41.77%, and the unfavorable category is 9.23%. 2) learning delivery strategy,values obtained with very good category was 43.92%, both categories was 40.77%, and the unfavorable category is 15.31%.3) learning management strategies, values obtained with very good category was 50.61%, both categories was 39.85%, andthe unfavorable category is 9.54%.